Development of a New Inflatable Controlled Anchor System and Experimental Study of pull-out Capacity - Xuexiang Yang; Shanpo Jia; Caoxuan Wen; Yuanjie Liu (Advances in Civil Engineering)
Considering the deficiency of traditional anchors, we propose a new type of inflatable controlled anchor system in this paper. The working mechanism and its structural composition of newly designed inflatable controlled device are discussed in detail. To investigate the performance and pull-out capacity of this new anchor system, a series of field tests were carried out under different inflation pressure conditions. By comparing these test results with those of traditional grouting anchors, a full-process constitutive model of anchor-soil interface is proposed to depict the pull-out characteristics of the inflatable controlled anchor. The results show that the ultimate bearing capacity of the inflatable controlled anchor is greater than that of the traditional grouting anchor when the inflation pressure is greater than 0.2 MPa and the ultimate bearing capacity of this new anchor improves obviously with the increase of inflation pressure. When the inflation pressure reaches 0.4 MPa, the ultimate bearing capacity of the inflatable controlled anchor is 2.08 times that of the traditional grouting anchor. Through comparison with the experimental curves, the results of model calculation indicate that the proposed anchor-soil interface constitutive equation can describe the pull-out characteristics of the inflatable controlled anchor. The designed controlled anchor has the advantages of no grouting, recyclability, rapid formation of anchoring force, and adjustable anchoring force.